Three-Phase Virtual Instrument Measurement System - Kim, Gan Chin; Abdullah, Abdul Rahim; Aripin, Muhamad Khairi (2006)
Electrical engineering laboratory often involves measurement of current and voltage signals. Conventionally, it is accomplished by using various types of hardwired measurement equipments. If further signals information is required the oscilloscope becomes the preference. However, for measurement of voltage that is connected to the mains, prior knowledge to isolation is a must. Conventional oscilloscopes neither have the isolation function nor the data logging capabilities for further analysis. This paper presents the hardware and software development of a custom-built three-phase measurement system, equipped with isolation and data logging features. It also includes a description of the application of virtual instrumentation, written in LabVIEW that uses the developed hardware. A case study will also be presented.